I HAVE BEGOTTEN YOU: PSALM 2:6-7 - Kabanga, Hokgie Kurniawan (Klabat Theological Review, 2022)
An accurate understanding of the yā∙lǎḏ ‘to beget’ and its original meaning as used in Psalm 2:7 may provide insight into a significant question: What is the significance of yülidTîºkä ‘I have begotten you’ in God’s salvific plan and what are the implications? This study seeks the biblical concept of the term ‘begotten’ in Psalm 2:7 and the theological implications which arise from a full understanding of the yülidTîºkä concept as the Psalmist uses it. As an exegetical and contextual study of yülidTîºkä may carry dynamic implications, this analysis reviews the authorship and dating of the Psalm, the genre, and the theme of the book. It discusses the literature structure, the grammatical study, the intertextual analysis, and the theology of the issue. Keywords: begotten, I have begotten you, incarnation, messiah, jesus, son of god, poetic literature, psalm 2:6-7